FAKTOR-FAKTOR YANG MEMPENGARUHI KETIDAKPATUHAN PAJAK BENDAHARA DESA DI KABUPATEN PONOROGO DENGAN MENGGUNAKAN PENDEKATAN THEORY OF PLANNED BEHAVIOR - Ibnu Fadhil, Mohamad Irvanuddin (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to determine the factors influencing non-compliance tax of village treasurers in Ponorogo. This study refers to the model of Theory of Planned Behavior (TPB). The variables of his study based on the TPB model, namely attitude, subjective norm, perceived behavioral control, moral obligation, intention and behavior.Samples of this study are 80 village treasurers in Ponorogo. Survey using questioner is used as a data collection method. The data of the study is analyzed using Partial Least Square (PLS).Hypothesis testing results show that attitude has a positive and not significant influence on intention to non-compliance behavior; while subjective norm has a positive and significant impact on intention to non-compliance behavior. It is also found that perceived behavioral control influences intention to non-compliance behavior positively and significantly; while moral obligation has a negative and not significant influence on intention to non-compliance behavior. Perceived behavioral control has a negative and not significant influence on non- compliance behavior. Lastly, intention to non-compliance behavior has a positive and significant effect on non-compliance behavior.Key word: Theory of planned behavior, attitude, subjective norm, perceived behavioral control, moral obligation, intention, tax noncompliance.